Knowledge, Attitudes, and Practices Toward the Prevention of COVID-19 in Bangladesh: A Systematic Review and Meta-Analysis - Raquib, Ahsan; Raquib, Radwan; Jamil, Safayet; Hossain, Ahmed; al-Mamun, Firoj; Mamun, Mohammed A. (Frontiers in Medicine, 2022)
Background: Numerous studies on knowledge, attitude, and practice (KAP) about the prevention of COVID-19 infections are available in Bangladeshi contexts, with results that vary significantly. However, no earlier attempt has been made to analyze the available COVID-19 KAP studies in Bangladesh, which is incorporated in this meta-analysis for the first time. Methods: Following the PRISMA guidelines, articles relevant to COVID-19 KAP that were conducted among the Bangladeshi population were found in databases such as PubMed, Scopus, CINAHL, Google Scholar, and ResearchGate. Random-effects meta-analysis was used to generate a pooled prevalence of knowledge, attitude, and practice level towards the prevention of COVID-19 infection. Results: This review included 18 articles that were published between March 2020 and November 2021. In the pooled data, there was inadequate knowledge of diarrhea as a symptom of COVID-19 infection (39.24%, 95% CI: 19.10-63.85), headache as a symptom of COVID-19 (56.23%, 95% CI: 49.80-62.46), and weakness as a symptom of COVID-19 (49.28%, 95% CI: 27.75-71.08). Overall, 89.87% (95% CI: 67.71-97.40) understood about COVID-19 symptoms, 92.09% (95% CI: 84.32-96.18) knew about how it spreads, and 79.51% (95% CI: 59.38-91.15) knew about how to treat it. The public's perception of controlling COVID-19 is mixed, with only 44.16% (95% CI: 35.74-52.93) and 60.28% (95% CI: 49.22-70.38) believing the country would win the struggle against the pandemic and the infection will be successfully controlled, respectively. Although overall COVID-19 preventative practice was good, sub-group analysis found that men had a poor practice towards controlling the infection. The practice of avoiding crowded places (70.15%) and maintaining social distance (77.17%) was found to be satisfactory in institution-based studies. Conclusions: The findings of this study revealed that the Bangladeshi population had a good awareness of COVID-19 symptoms, treatment, attitudes, and behaviors. The findings of this study are likely to aid Bangladeshi governments and policymakers in putting evidence into action by identifying gaps and emphasizing the importance of educating the less informed public about COVID-19 transmission.